Correlation between Motivation and Professional Identity of Medical Students of Universitas Swadaya Gunung Jati, Cirebon, Indonesia - Mega Silvia Maulidia Mustopa; Tissa Octavira Permatasari; Catur Setya Sulistiyana (GHMJ (Global Health Management Journal))
Background: Professional identity plays an important role for doctors in their practice. The important role of professional identity in medical education, namely learning the professionalism of doctors and being responsible for the duties of being a student and the rules that make it more responsible to patients. Professional identity is influenced by external and internal factors, one of which is motivation which plays an important role in medical education can foster creativity which makes the learning process a transformational experience that is important for the development of a strong professional identity. Objective: To determine the relationship between motivation and professional identity of students of the Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia.